Penerapan Green Accounting dan CSR terhadap Eksistensi Usaha Ayam Petelur dengan Komitmen Pengusaha sebagai Pemoderasi - Syukri, Muhammad; Fitri, Syarifah Massuki; Yuliartika, Dina; Anisaputri, Eka (LPPM Institut Pendidikan Nusantara Global, 2025)
The egg-laying chicken business is a sector with high potential for environmental impacts, thus requiring the implementation of sustainable business practices. This study was conducted to analyze the effect of Green Accounting and Corporate Social Responsibility (CSR) implementation on the existence of egg-laying chicken businesses, as well as to examine the role of entrepreneur commitment as a moderating variable. The study used a quantitative approach with a descriptive verification method. The research sample consisted of 100 egg-laying chicken entrepreneurs in Lingsar District, West Lombok Regency, which were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique with the assistance of SmartPLS 3.0 software. The results showed that the implementation of CSR had a significant positive effect on business existence, while Green Accounting had no significant effect. Entrepreneur commitment also had a positive effect on business existence, but did not moderate the relationship between Green Accounting and CSR on business existence. This finding confirms that the sustainability of egg-laying chicken businesses is more influenced by corporate social responsibility.